Cellulose fibrils formation and organisation of cytoskeleton during encystment are essential for Acanthamoeba cyst wall architecture - Garajová, Mária; Mrva, Martin; Vaškovicová, Naděžda; Martinka, Michal; Melicherová, Janka; Valigurová, Andrea (Scientific reports, 2019)
Acanthamoebae success as human pathogens is largely due to the highly resistant cysts which represent a crucial problem in treatment of Acanthamoeba infections. Hence, the study of cyst wall composition and encystment play an important role in finding new therapeutic strategies. For the first time, we detected high activity of cytoskeletal elements - microtubular networks and filamentous actin, in late phases of encystment. Cellulose fibrils - the main components of endocyst were demonstrated in inter-cystic space, and finally in the ectocyst, hereby proving the presence of cellulose in both layers of the cyst wall. We detected clustering of intramembranous particles (IMPs) and their density alterations in cytoplasmic membrane during encystment. We propose a hypothesis that in the phase of endocyst formation, the IMP clusters represent cellulose microfibril terminal complexes involved in cellulose synthesis that after cyst wall completion are reduced. Cyst wall impermeability, due largely to a complex polysaccharide (glycans, mainly cellulose) has been shown to be responsible for Acanthamoeba biocide resistance and cellulose biosynthesis pathway is suggested to be a potential target in treatment of Acanthamoeba infections. Disruption of this pathway would affect the synthesis of cyst wall and reduce considerably the resistance to chemotherapeutic agents.
Keywords: buněčná membrána; cytoskelet; Humans; Microscopy, Electron; Microscopy, Confocal; celulosa; amébiáza; konfokální mikroskopie; Microtubules; Acanthamoeba; lidé; mikrotubuly; Amebiasis; Cellulose; buněčná stěna; elektronová mikroskopie; Cell Membrane; Cytoskeleton; Cell Wall